Cyber Security In 2023: The Latest Challenges And Solutions - Wiratama, Ahmad Doni (Jurnal Komputer Indonesia, 2023)
Cybersecurity has become a crucial issue in the digital age, especially in 2023 where technology continues to evolve rapidly. This article discusses the challenges faced in maintaining cybersecurity, such as the rise of increasingly sophisticated cyberattacks, and the latest solutions offered to deal with them. The research was conducted through literature analysis as well as relevant case studies. The results show that new approaches such as Zero Trust, artificial intelligence in threat detection, and collaboration between entities are key to strengthening cybersecurity in 2023.